Policies for Macrofinancial Stability : Options to Deal with Real Estate Booms - Dell'Ariccia, Giovanni; Crowe, Christopher; Igan, Deniz; Rabanal, Pau. (Washington, D.C. : International Monetary Fund, 2011)
DISCLAIMER: This Staff Discussion Note represents the views of the authors and does not necessarily represent IMF views or IMF policy. The views expressed herein should be attributed to the authors and not to the IMF, its Executive Board, or its management. Staff Discussion Notes are published to elicit comments and to further debate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Markets and the Macroeconomy; Prices, Business Fluctuations, and Cycles